A Study on English Learning Motivation of Chinese Philosophy Majors - Hu, Yaqi; Ma, Anning; Zhu, Jiajun (Transactions on Social Science, Education and Humanities Research, 2024)
In this paper, 102 sophomores and juniors from 11 universities in southern China were selected to study the relationship between English learning motivation and its effects among Chinese philosophy majors. SPSS data analysis software was then used to analyze the collected data by frequency analysis, cross-analysis and linear regression analysis to explore the correlation among learning motivation, methods and effects. The analysis showed several main learning motivations and their corresponding learning methods. The results showed that the top three motivations were "for school exams", "for studying English literature of philosophy" and "for school exams". Among them, students who take “for studying English literature of philosophy" or "for school exams" as English learning motive will not take any specific way to learn English and students who take the "for studying abroad examinations" as their motivation for English learning generally adopts a specific way to study English, which is "situational communication". In addition, there is no significant correlation between learning methods and learning outcomes, and an obvious correlation between learning motivation and learning outcomes.